Repurposing of Metformin to Improve Survival Outcomes in Patients With Upper Tract Urothelial Carcinoma - Hsiang Ying Lee; Po‐Hung Lin; See‐Tong Pang; Jen‐Kai Fang; Chung‐You Tsai; Yao‐Chou Tsai; Yung‐Tai Chen; Wei‐Chieh Chen; Hsin‐Chih Yeh; Wei‐Ming Li (Cancer Medicine)
ABSTRACT Purpose Upper tract urothelial carcinoma (UTUC) presents a higher incidence rate in Taiwan compared to Western societies. The aim of this study is to investigate the potential of metformin in improving survival outcomes for patients with UTUC in Taiwan. Material and Methods This retrospective study included 940 patients with UTUC and type 2 diabetes from the Taiwan UTUC Collaboration Group, spanning 21 hospitals from July 1988 to September 2023. Patients were divided into two groups: those treated with metformin (n = 215) and those without metformin treatment (n = 725). Parameters analyzed included age, BMI, renal function, tumor grade and location, and pathological staging. Oncological outcomes measured were overall survival (OS), cancer‐specific survival (CSS), and bladder recurrence‐free survival (BRFS). Statistical analysis involved the use of Student's t‐test, Mann–Whitney test, Chi‐squared test, Fisher's exact test, and Cox proportional hazard regression. Results Significant differences were observed between the two groups in BMI, preoperative creatinine, eGFR, tumor location, tumor laterality, tumor size, and pathological grade and T stage. Patients treated with metformin exhibited a lower risk of CSS (HR = 0.619; p = 0.018) and improved OS (HR = 0.713; p = 0.024), although no significant association was found with BRFS (HR = 1.034; p = 0.791). The protective effect of metformin on OS was particularly significant in patients with advanced T stage, metastasis, and high‐grade tumors. Conclusion The study suggests that metformin use in UTUC patients with diabetes is associated with improved OS and CSS but not BRFS. The underlying mechanisms warrant further investigation. Repurposing metformin, a well‐established and safe drug, may develop new therapeutic strategies for UTUC.